2016
DOI: 10.3892/etm.2016.3862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral intake of heat-killed Lactobacillus brevis SBC8803 (SBL88™) on dry skin conditions: A randomized, double-blind, placebo-controlled study

Abstract: Lactobacilli are important in intestinal homeostasis, which involves the regulation of immune function, digestive health, cholesterol absorption and intestinal tumor growth amongst others. Our previous investigations have suggested that oral intake of heat-killed Lactobacillus brevis (L. brevis) SBC8803 (SBL88™) suppresses dermatitis by modulating the immune function in an atopic dermatitis mouse model. The aim of the present study was to investigate the effect of heat-killed L. brevis SBC8803 intake on skin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Several studies demonstrated that HP‐positive samples exhibited decreased gastric microbiotic diversity; this suggests that HP infection may likely trigger dysbiosis of the gut microbiota, which in turn affects the immune system, potentially initiating the development of CSU. Various skin diseases such as acne, atopic dermatitis, and psoriasis are considered as examples of dysbiosis and oral probiotics improved skin symptoms in several studies . Intestinal microbiota is considered to modulate skin dyshomeostasis via gut‐skin axis, possibly by inducing systemic immunity to gut bacteria and migration of such bacteria to the skin via the bloodstream .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that HP‐positive samples exhibited decreased gastric microbiotic diversity; this suggests that HP infection may likely trigger dysbiosis of the gut microbiota, which in turn affects the immune system, potentially initiating the development of CSU. Various skin diseases such as acne, atopic dermatitis, and psoriasis are considered as examples of dysbiosis and oral probiotics improved skin symptoms in several studies . Intestinal microbiota is considered to modulate skin dyshomeostasis via gut‐skin axis, possibly by inducing systemic immunity to gut bacteria and migration of such bacteria to the skin via the bloodstream .…”
Section: Discussionmentioning
confidence: 99%
“…This effect was reproduced in human clinical research. After taking L. brevis SBC8803 oral supplements for 12 weeks, human subjects had significantly decreased TEWL and significantly increased corneal hydration ( Ogawa et al, 2016 ). In a separate placebo-controlled human study, bacterial supplementation was shown to have a positive effect on skin barrier function ( Guéniche et al, 2013 ).…”
Section: Role Of the Gut Microbiome In Skin Homeostasismentioning
confidence: 99%
“…Interestingly, such experimental evidence was also observed in human clinical trials. Oral supplementation of L. brevis SBC8803 for 3 months could profoundly reduce TEWL and increase epidermal hydration in human subjects (Ogawa et al, 2016). The findings of a clinical trial showed that barrier function of cutaneous could be positively affected by bacterial administration (Gueniche et al, 2013).…”
Section: Gastrointestinal Microbiota and Skin Healthmentioning
confidence: 99%